The Effect of Organizational Climate, Job Satisfaction, and Work Engagement on Employee Performance at PT Hasta Dwiyustama - Afdhila, Riska Nur; Bakti, Dadang Karya; Saptiani, Fenny (Journal of Business Management and Economic Development, 2025)
This study aims to examine how organizational climate, job satisfaction, and work engagement effect employee performance at PT Hasta Dwiyustama. The research applies a quantitative approach with an explanatory research design. The sampling technique used in this study was total sampling, in which all 32 employees of PT Hasta Dwiyustama were selected as respondents. The data consists of both primary and secondary sources. Data collection was conducted through the distribution of questionnaires using a Likert scale. The collected data were then analyzed using multiple linear regression. The results indicate that, partially, organizational climate and work engagement have a significant effect on employee performance. In contrast, job satisfaction does not show a significant effect on employee performance at PT Hasta Dwiyustama. Simultaneously, the three variables organizational climate, job satisfaction, and work engagement together have a significant effect on employee performance at the company. It is recommended that the company provide competency test programs to support employees in preparing for promotion opportunities. Future researchers are advised to conduct studies with a larger sample size and consider other potentially influential variables.